(untitled) (Makerere University Journal of Agricultural & Environmental Sciences, 2004)
A total of seventy farmer-saved rice seed samples from three districts of Uganda namely Bugiri, Pallisa, and Lira were examined for purity and germination following procedures described by the International Seed Testing Association. The results revealed that postharvest handling practices (threshing, drying and storage) significantly (P<0.001) affect the quality of rice seed and their effects are additive as indicated by observed significant differences for the 2 and 3-way interaction effects of storage and threshing, and storage, threshing, and drying, respectively. Threshing by “beating” significantly reduced the quality of the seed while drying on cemented floors and polyethylene sheets reduced the germination percentage but maintained the physical purity of the seed. Rice seed stored in polyethene and polyline bags exhibited the highest proportion for germination and purity tests. Thus, postproduction operations needed to be considered as part of an approach to minimise losses in quality of farmer saved rice seeds.